Hypoxic Induction of Anoxia Tolerance in Root Tips of Zea mays - Johnson, James (1989)
When root tips of fully aerobic, intact maize (Zea mays L.) seedlings are made anaerobic, viability normally is only 24 hours or less at 25°C. We find that viability can be extended to at least 96 hours if seedlings are given a hypoxic pretreatment for 18 hours by sparging the solution with 4% O(2) in nitrogen (v/v) before anoxia. Fully aerobic root tips (sparged with 40% O(2)) had very low alcohol dehydrogenase (ADH) activity (per gram root fresh weight), and the level remained low under anoxia. In hypoxically pretreated roots, however, high levels of ADH activity were induced, and activity rose further during the initial 24 hours of anoxia, and then remained high at about 20 times that of controls in 40% O(2). ADH activity in roots in solution sparged with air (21% O(2)) was about three times that in 40% O(2). Improved viability of hypoxically pretreated root tips was associated with maintenance of a high energy metabolism (ATP concentration, total adenylates, and adenylate energy charge). Roots that were not pretreated lost 94% of the total adenylates and ATP at 24 hours of anoxia. The relation between induced ADH activity, energy metabolism, and improved anoxia-tolerance in acclimated maize root tips is discussed.